On some new paranormed sequence spaces of fuzzy numbers defined by Orlicz functions and statistical convergence - Esi, A. (Mathematical Modelling and Analysis, 2006)
In this paper we introduce the concept of strongly λ(p) convergence of fuzzy numbers with respect to an Orlicz function and examine some properties of the resulting sequence spaces and λ(p) – statistical convergence. It is also shown that if a sequence of fuzzy numbers is strong λ(p) convergent with respect to an Orlicz function then it is λ(p) – statistically convergent. First Published Online: 14 Oct 2010